Narrativity and the Symbolic Vacuum - Lukits, Stefan (Philosophy & theology, 2011)
“Narrativity and the Symbolic Vacuum” examines the descriptive and the prescriptive narrativity claim in the context of a claim that there are narratives in the biblical literature that resist both. The descriptive narrativity claim maintains that it is not an option for a person to conceive of their life without narrative coherence. The prescriptive claim holds that narrativity is a necessary condition for a good and successful human life. Phenomenological thought and Aristotelian virtue ethics, expressing a critical stance towards modernity (modernity with its desire for objective, narrative-free criteria for truth), encourage narrativity claims. Biblical theology, despite its pervasive use of narrative strategies, offers a space in which narrativity claims are relativized. It is especially in confrontation with death where human life cannot be narratively managed. That is why it is in particular the cross in the New Testament which defies both descriptive and prescriptive narrativity claims.